(untitled) (International Journal of Engineering and Computer Science, 2014)
This paper presents a survey on Security in Cloud Computing. This discussion is centered on overview of Cloud Computing threats, issues, security in cloud communication, infrastructure security, management in cloud. Cloud computing as we know is envisioned of the next-generation technology of IT industry. Cloud computing can be used by a prospective Cloud service for analyzing the data security risk before putting the confidential data into a cloud computing environment